Efficacy and safety of external trigeminal neurostimulation in the prevention of chronic migraine: An open-label trial - Marius Birlea; Sophie Penning; Kyle Callahan; Jean Schoenen (SAGE Publishing, 2019)
Objective: This trial explored the therapeutic utility and safety of external trigeminal neurostimulation (eTNS) as a preventive treatment in patients suffering from chronic migraine (CM). Methods: It was a monocenter, prospective, open-label, pilot trial conducted at the University of Colorado, Anschutz Medical Campus (Aurora, CO, USA). Participants were adult patients with a history of CM meeting International Classification of Headache Disorder-3 beta (2013) diagnostic criteria with or without medication overuse. After a 1-month baseline period, the patients still fulfilling the inclusion criteria applied at least one daily 20-min session of eTNS for 3 months. Primary outcomes were mean monthly changes in frequency of headache days and in overall acute headache medication intake. Results: Eighty patients were assessed for eligibility, 73 were included in the baseline period after which 58 entered the treatment period and were included in the intention-to-treat analysis. Compared to baseline, frequency of headache days decreased by −3.12 days (−16.21%, p < 0.001) and acute medication intake decreased from 26.33 to 18.22 (−30.81%, p < 0.001) during the third month of treatment. Twenty-six patients reported 47 minor adverse events, of which only 2 were related to the use of the device (skin irritation under the electrode and headache worsening with vertigo). Conclusions: This trial suggests that eTNS is safe and effective as prophylactic treatment for CM and indicates that a randomized sham-controlled trial is worthwhile. Trial registration: ClinicalTrials.gov (identifier: NCT02342743).